Respuesta :

frika

Answer:

[tex](x-1)^2+(y+2)^2=25.[/tex]

Step-by-step explanation:

If the center of the circle is (1,-2) and the circle passes through the point (4,2), then the radius of the circle is

[tex]r=\sqrt{(1-4)^2+(-2-2)^2}=\sqrt{9+16}=5.[/tex]

The equation of the circle with center [tex](x_0,y_0)[/tex] and radius r is

[tex](x-x_0)^2+(y-y_0)^2=r^2.[/tex]

In your case, the equation is

[tex](x-1)^2+(y+2)^2=25.[/tex]

Answer:

(x-1)²+ (y+2)² = 25 is the equation of circle.

Step-by-step explanation:

We have given the center (1,-2) and a point P (4,2) from which the circle is passes.

So, the radius of the circle is :

[tex]r = \sqrt{(4-1)^{2}+(2-(-2))^{2}}=\sqrt{25}=5[/tex]

The equation of circle is :

(x - x₁)² +(y - y₁)² = r²     where (x₁,y₁) is the center of circle.

Putting the value in above equation we get,

(x-1)²+(y-(-2))² = (5)²

(x-1)²+ (y+2)² = 25 is the equation of circle.